Mmp17-deficient mice exhibit heightened goblet cell effector expression in the colon and increased resistance to chronic Trichuris muris infection - Vornewald, Pia M.; Forman, Ruth; Yao, Rouan; Parmar, Naveen; Lindholm, Håvard T.; Lee, Lilith S. K.; Martín-Alonso, Mara; Else, Kathryn J.; Oudhoff, Menno J. (Frontiers in Immunology, 2023)
Intestinal epithelial homeostasis is maintained by intrinsic and extrinsic signals. The extrinsic signals include those provided by mesenchymal cell populations that surround intestinal crypts and is further facilitated by the extracellular matrix (ECM), which is modulated by proteases such as matrix metalloproteinases (MMPs). Extrinsic signals ensure an appropriate balance between intestinal epithelial proliferation and differentiation. This study explores the role of MMP17, which is preferentially expressed by smooth muscle cells in the intestine, in intestinal homeostasis and during immunity to infection. Mice lacking MMP17 expressed high levels of goblet-cell associated genes and proteins, such as CLCA1 and RELM-b, which are normally associated with immune responses to infection. Nevertheless, Mmp17 KO mice did not have altered resistance during a bacterial Citrobacter rodentium infection. However, when challenged with a low dose of the helminth Trichuris muris, Mmp17 KO mice had increased resistance, without a clear role for an altered immune response during infection. Mechanistically, we did not find changes in traditional modulators of goblet cell effectors such as the NOTCH pathway or specific cytokines. We found MMP17 expression in smooth muscle cells as well as lamina propria cells such as macrophages. Together, our data suggest that MMP17 extrinsically alters goblet cell maturation which is sufficient to alter clearance in a helminth infection model.